Criterion of Foundation of Norms as Norms of Good Practices - Ignace Haaz (Journal of Ethics in Higher Education)
Norms are based on rigour and principles; norms don’t depend on values. Facts’ determination on norms should be limited to strict knowledge of these determinations, which are never normative justifications. However, values may or may not have normative power, but even without normative power, values make us who we are as human beings, on the background of attachments which shape more irrationally our psyche as affects. Rights compared to principles bring back the idea that some determinations cannot be taken away of the definition of norms, instead rights invite us for a compromise, when factual determinations as inequalities impact in unjust ways duties and authorisations, a right-based approach tend to bring light to theses unfair conditions and invite for a redefinition, not following essentially the commandment of rights but rules that are thought to prevent chaotic transition from one set of rules or principles to an other rule corresponding better to a new situation in the world.